Faidherbia albida and its effects on Ethiopian highland Vertisols - Kamara, C.S.; Haque, I. (Springer, 1992)
This paper reports on studies of Faidherbia albida trees and their effects on some properties of vertisols in the Ethiopian highlands. The study was carried at the experiment station of ILCA at Debre Zeit with 850 mm rainfall and at an altitude of 1850 m. Studies on the lateral and vertical influence of the tree canopy on some physical and chemical properties of the soil show apparent higher organic matter on the west side of the tree than the east due to accumulated wind blown litter by prevalent wind direction, and organic matter, N, P and K levels were higher under the tree canopy than outside for all directions and depths studied. Soil Ph, exchangeable Na, Ca and Mg under the canopy and outside were similar. Available water capacity was 1.5 to 2 times more under than outside the tree. Noticeable increases in the silt fraction under the tree was recorded and discussed in relation to soil condition improvement and plant growth.